Exploring fourth graders' sourcing skills / Un análisis de la capacidad de escrutinio sobre las fuentes de información de los estudiantes de cuarto grado. Issue 3 (3rd July 2018) - Paul, Johanna; Cerdán, Raquel; Rouet, Jean-François; Stadtler, Marc
Abstract: Acquiring information from the Web creates new educational demands even in elementary school. Children need to scrutinize source information ('sourcing') to choose trustworthy information. So far, few studies have documented young readers' abilities to identify and evaluate source information. With two studies, we seek to gather more evidence on elementary students' sourcing skills and use. In study 1, we investigate to what extent fourth graders can identify source information and evaluate informants' expertise and intentions in simplistic, age-appropriate reading tasks. In study 2, we explore whether fourth graders spontaneously apply their sourcing skills when reading simplified multiple documents. Results suggest that fourth graders can successfully identify source information and evaluate informants' expertise and intentions in simple and direct tasks but fail to apply this ability to more complex and implicit tasks. Implications for information literacy education are discussed.